A Smooth Transition: A Phenomenological Approach to Understanding the Experiences of First‐time, Full‐time, Provisionally Accepted Black Male Students - Jackson, Nikki Nacole (My University, 2017)
The purpose of this study was to investigate first-time, full-time provisionally accepted Black male students and to achieve a clear understanding of their lived experiences to enhance campus-wide social network systems, student engagement, cognitive dissonance and self-efficacy to improve opportunities for academic success. This study is significant because it explores the gap in existing literature and research on the impact of Black male students’ precollege characteristics, experiences, and perceptions of their academic success and self-efficacy. Notable retention theorists Astin (1984), Bean (1985), and Tinto (1993) provided a great introduction of the issues affecting retention and the barriers impacting students’ desire to persist, but there is a gap in the research. These issues include, but are not limited to, lack of academic and social involvement, failure to adapt, and self-efficacy. Students’ admission type seems to be overlooked in the literature. To gain an in-depth understanding of the lived-experiences of first-time, full-time, provisionally accepted Black male students and to discover the essence of those experiences while providing a platform for implementing new policies, procedures, and, if necessary, pedagogy for state colleges and state universities and their social network systems within the University System of Georgia (USG), Georgia’s public colleges and universities, I conducted a phenomenological study. Eight participants were interviewed at four USG schools. Two were state colleges and two were state universities. Data was collected through in-depth interviews and focus groups addressing the three research questions related to this study: 1) What are the lived experiences of provisionally accepted, first-time, full-time, Black male students within their first academic year at state colleges and state universities in Georgia? 2) What are the common perceptions of provisionally accepted, first-time, full- time, Black male students that influence their academic success at state colleges and state universities within the University System of Georgia? 3) How do social network systems, student engagement, cognitive dissonance and self-efficacy affect first-time, full-time provisionally accepted, Black males’ academic success?
Chapter I: INTRODUCTION… 1 | Research Questions… 5 | Significance of Study 6 | Conceptual Framework 6 | Chapter II: LITERATURE REVIEW 10 | Paying for College 13 | Organizational Impact on Student Learning 14 | State Colleges and State Universities… 15 | Student Engagement… 16 | Precollege Experiences and First-year Students… 20 | Social Network Systems… 21 | Self-Efficacy 24 | Departure and Change 28 | Chapter III: METHODOLOGY 31 | Research Design… 32 | Phenomenology 32 | Sampling Techniques… 32 | Site Selection… 32 | Participant Selection… 33 | Data Collection Procedures… 34 | Interviews… 35 | Pilot Interviews… 36 | Focus Groups… 37 | Data Analysis Procedures… 39 | Coding 40 | Biases… 41 | Trustworthiness… 42 | Triangulation… 43 | Reflexivity 44 | Bridling 44 | Chapter IV: INTRODUCTION OF RESULTS 48 | Results of Interviews with Participants with Low EFC Scores… 48 | Brief Profiles of Low EFC Participants… 50 | Precollege Experiences and Characteristics and Student Engagement… 75 | Social Network and Student Engagement… 80 | Persistence and Academic Success… 84 | Chapter V: RESULTS OF HIGH EFC PARTICIPANTS 86 | Brief Profiles of High EFC Participants… 88 | Precollege Experiences and Characteristics and Student Engagement… 105 | Social Network and Student Engagement… 109 | Persistence and Academic Success… 113 | Chapter VI: SUMMARY OF FINDINGS 117 | Research Question 1… 117 | Now and Then: The Learning Curve: Skill and Experience 117 | Intervention and Prevention… 121 | Research Question 2… 123 | Provisional Opportunity 123 | Partnerships… 126 | Academic Success… 127 | Mind over Matter… 128 | Research Question 3… 129 | Elect to Disconnect… 129 | Chapter VII: DISCUSSIONS AND CONCLUSIONS 133 | Discussion… 134 | Making a Connection with Success… 135 | At-risk for Success… 138 | Research Question 2 139 | A Provisional Opportunity 139 | Family Matters… 141 | Research Question 3 142 | A Success Story 142 | Preferred Disengagement… 143 | Improvement of Communications… 144 | Limitations of the Study 145 | Implications for Practice 145 | Recommendations for Future Research… 147 | REFERENCES 150 | APPENDICES 158 | Appendix A: Valdosta State University Institutional Review Board Approval… 158 | Appendix B: Email to Participants… 160 | Appendix C: Valdosta State University Consent to Participate 162 | Appendix D: Interview Protocol… 166 | Appendix E: Interview Questions… 169 | Appendix F: Skype Protocol… 172 | Appendix G: Focus Group Questions… 174 |
Keywords: Dropouts--Prevention; Self-efficacy; Social networks; Academic achievement